Pope Francis' Vision for Education and the Call for a Global Compact on Education - Klein, Luiz Fernando (The review of faith & international affairs, 2023)
In September 2019, Pope Francis called for a broad alliance to renew our commitment to education to build a more fraternal humanity. To understand the Pope’s call for a Global Compact on Education, it is useful to explore his vision for education. For Pope Francis, education can no longer be reduced to what happens in the classroom. We need educational strategies that give a chance to the transformation and above all to the humanization of the world. We need an “education village” in which parents, communities, and societies are fully engaged. The call for a Global Compact on Education can be understood as a new paradigm for thinking about education.